”Sound alternations discussed by Ibn Jenni” in his book “attanbeih ala ʃarħ muʃkila:t alħamasah - Al-Amri, Salman Ali (Arab Journal for Sciences and Research Publishing, 2018)
This research aims to explore seven sound alternation issues that are discussed by the Arab old grammarian “Ibn Jenni” in his book attanbeih ala ʃarħ muʃkila:t alħamasah [Focus on the interpretation of the book of alħamasah (enthusiasm) by Ibn Jenni]. Sound alternation is a vast topic that has attracted the attention of a large number of old and modern Arab linguists. In this paper, I discuss these seven issues that received special attention from Ibn Jenni in his book by briefly reporting his viewpoints about each issue and his method in discussing it. In addition, the viewpoints of other grammarians (morphologists) are also discussed in enough details explaining the ones who agree with him and those who disagree. Finally, I comment on these issues and illustrate which arguments I believe are more solid and why.
Keywords: Ibn Jinni; Morphology; Substitution; Warning